Transmission of Ultrasonic Waves in Optical Fibers with the Use of Sandwich Type Transducer - MUC, Sylwia (Archives of Acoustics, 2009)
Optical fibers are commonly used to transmit laser beams. The possibility of acoustic wave propagation in optical waveguides creates new prospects for simultaneous transmission of laser beams and ultrasonic waves. This combined technology could be useful in e.g. surgical treatment. A comparative analysis of both systems shows that combining the advantages of ultrasounds and laser light in one device, makes it possible to compensate for the faults of each of the technologies and to improve the effectiveness of surgical operations. The article presents the results of experimental studies of transmission of ultrasonic wave in optical fibers using a sandwich-type ultrasonic power transducer. It also presents amplitude characteristics of an ultrasonic signal propagated in an optical fiber. The effect of the length of the fiber on the achieved output signal amplitudes was studied. The relation of the output signal of a capacitive sensor to the power applied to the sandwich-type transducer was presented. The reflected power during ultrasonic wave propagation in an optical fiber was also measured. The measurements of the ultrasonic wave transmission were performed for single-mode and multi-mode step-index optical fibers.